Insights into the Adhesive Mechanisms of Tree Frogs using Artificial Mimics. (9th October 2012) - Drotlef, Dirk‐Michael; Stepien, Lukas; Kappl, Michael; Barnes, W. Jon P.; Butt, Hans‐Jürgen; del Campo, Aránzazu
Abstract Elastic, microstructured surfaces (hydrophobic and hydrophilic) mimicking the surface structure of tree‐frog toe‐pads are fabricated. Their adhesion and friction behaviour in the presence of a liquid layer is evaluated and compared to flat controls. Tree‐frog‐like patterns are beneficial for wet adhesion only if the liquid does not wet the surface. The situation is different in friction, where the surface structure lead to significantly higher friction forces only if the liquid does wet the surface. Taking into account that tree‐frog attachment pads are hydrophilic and that their secretion wets all kind of surfaces, our results indicate that the surface structure in tree‐frog toe‐pads has been developed for climbing, when shear (friction) forces are involved. These results evidence the benefits and limitations of the surface design (microstructure and hydrophilicity) for adhesion and friction under wet conditions.